2003
DOI: 10.1055/s-2003-42375
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Scanning in Sarcoidosis

Abstract: Sarcoidosis is a granulomatous disease of unknown etiology that involves the lungs or intrathoracic lymph nodes in more than 90% of patients. The clinical spectrum of sarcoidosis is protean, but pulmonary manifestations often dominate. Chest radiographs are abnormal in 90 to 95% of patients with sarcoidosis; the most characteristic feature is bilateral hilar lymphadenopathy (BHL), present in 50 to 80% of patients. Pulmonary parenchymal infiltrates are present in 25 to 50% of patients. In this article, we revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 99 publications
(283 reference statements)
1
5
0
Order By: Relevance
“…Scadding staging was assessed with chest roentgenograms. Although computed tomography is more sensitive for detecting fibrotic changes in the lungs of sarcoidosis patients [43], the number of missed Stage IV cases is likely small [44]. Given the large number of Scadding Stage IV cases in our analysis (n = 190), such misclassification would likely have nominal effects on our results.…”
Section: Discussionmentioning
confidence: 96%
“…Scadding staging was assessed with chest roentgenograms. Although computed tomography is more sensitive for detecting fibrotic changes in the lungs of sarcoidosis patients [43], the number of missed Stage IV cases is likely small [44]. Given the large number of Scadding Stage IV cases in our analysis (n = 190), such misclassification would likely have nominal effects on our results.…”
Section: Discussionmentioning
confidence: 96%
“…Higher serum ACE could indicate higher monocytic cell line activity or granulomatous inflammation [ 21 ]. The predictive value of ACE for diagnosing sarcoidosis is 47%, lower than that of chest radiographic findings [ 22 , 23 ]. Although there was no statistical significance, the rate of increased ACE level and mean ACE level was slightly higher in the group with ocular involvement in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our hypothesis, studies have shown that parenchymal biopsies obtained from MNs in sarcoidosis patients revealed non-caseating granulomas. It is also well known that the shape of granulomas is usually round and their dimensions may vary from micrometers to millimeters [2,8,13,14]. Also, due to systemic nature of the disease, every single organ or system might be involved to some extent in sarcoidosis, even though we could not visualize all these possible localizations of the disease by conventional imaging/screening methods, because they can be too small in some organs or systems to be visualized with these techniques [3,15].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the demonstration of MNs might be considered as a good example for this condition in sarcoidosis patients. In many studies it was shown that the distribution of MNs was perilymphatic in HRCTs of patients with pulmonary sarcoidosis [3,5,8,14-16]. That is : MNs are mostly located in sub pleural regions, in broncho vascular bundles and sometimes in interlobular septae [3,8,16] indicating that the disease is related to lymphatic system from another point of view.…”
Section: Discussionmentioning
confidence: 99%